Mass Modeling of Indian Coffee Plum (Flacourtia Jangomas) Fruit with Its Physicochemical Properties. (21st September 2020) - Barbhuiya, Rahul Islam; Nath, Debarshi; Singh, Sushil Kumar; Dwivedi, Madhuresh
ABSTRACT: Flacourtia jangomas (Lour.) Raeush: is an underutilized fruit of India frequently found in the Barak valley of Assam and nearby areas of the north-eastern part of the country. It has good medicinal, nutritional and economic value. The research was conducted to investigate the physical, mechanical, biochemical and thermal properties of the fruit and to determine the mass modeling of the fruit depending on its various dimensional attributes. Models like S-curve, Power and Quadratic models were used to predict the mass of the fruit. It was found that mass could be predicted best when models were based on length, thickness and volume. The quadratic and power models showed the best relation between the mass and dimensional parameters of the fruit. The physicochemical characterization and mass modeling of the Indian coffee plum fruit would help in the design and development of various processing, handling, and storage equipment.